Effect of Cystocele Repair on Cervix Location in Women With Uterus In Situ. Issue 1 (January 2018) - Swenson, Carolyn W.; Morgan, Daniel M.; George, Jenny; DeLancey, John O.
Abstract : Introduction and Hypothesis: Our objective was to test the hypothesis that cystocele repair, in the absence of hysterectomy or apical suspension, results in higher cervix location in some women. Methods: We performed a retrospective chart review of women with a uterus in situ who underwent native tissue anterior repair without hysterectomy/apical suspension from 2008 to 2014. Demographics, medical history, and preoperative and 6-week postoperative Pelvic Organ Prolapse Quantification System measurements were abstracted. Cervix location was defined by the clinic Pelvic Organ Prolapse Quantification System point C value. Women with higher (more negative) postoperative point C values were compared with those with a lower (more positive)/unchanged point C. Results: Of the 33 women included, mean age was 59.8 ± 11.3 years. Median preoperative point C was −6.0 (interquartile range [IQR]: −6.75, −5.0) and point Ba was +2.0 (IQR: +0.5, +3.0). Point C was higher postoperatively in 21 (64%) of 33 women. Overall, point C was 1 cm higher post- versus preoperatively (−7.0 [IQR: −8.0, −6.0] vs −6.0 [IQR: −6.75, −5.0], P < 0.001) and point Ba was 4 cm higher (−2 [IQR: −3.0, −2.0] vs 2.0 [IQR: 0.5, 3.0], P < 0.001). Compared with women with lower/unchanged postoperative point C, those with higher point C were older (53.9 ± 12.3 vs 63.1 ± 9.4, P = 0.02) with lower parity (3.0 [IQR: 2.0, 3.0] vs 2.0 [IQR: 2.0, 3.0], P = 0.028). Conclusions: The test of our hypothesis shows that in certain women with cystocele, anterior repair alone may be associated with higher cervix location 6 weeks postoperatively. Abstract : Cystocele repair alone results in higher postoperative cervix location in some women with a uterus in situ.